Technological development for the optimization of the extraction of pecan nuts - Morales Magallanes, Humberto; Landeros Soriano, César; Villegas Berúmen, Héctor Gabriel (Revista Mexicana de Ciencias Agrícolas, 2020)
The objective of this article is to show the results derived from a proposal for the optimization of the extraction process of the Carya illinoinensis Koch walnut, implementing the use of technological development as a fundamental part of the process. The foregoing, in search of new technological tools for the producers of this fruit and thus contribute to economic development by reducing costs, increasing efficiency and increasing production by optimizing processes. This investigation takes as a sample a local producer located in the rural community ‘Lo de Nava’, Jerez de García Salinas, Zacatecas. To carry out the extraction process, 100 walnut samples were analyzed, of which 45 had the extraction process applied manually and the remaining 55 had an optimized process for the separation of the almond, this with in order to collect the data for statistical analysis and know the results of the research approach. That said, the proposal to address the problems outlined is the development of a mechanized process whose objective is to adequately separate the almond and the shell, derived from an analysis of internal structural efforts that facilitate the process of obtaining the fruit, the increased production and improvements in marketing. The statistical method used for the data analysis is Chi square (X2 calculated= 8.13, which is greater than X2 critical= 3.841), with a level of significance (α= 0.05), so the decision is in the rejection zone for H0; satisfying the acceptance of the alternative hypothesis H1. The results show that the implementation of technological development in the walnut extraction process depends on the method used for said process, since with this implementation there is a greater extraction of the entire fruit in less time, obtaining higher quality in relation to the processes reviewed in this investigation; this is reflected in the increase in sales, as it has a competitive advantage that fosters the development of producers. It is concluded that companies should focus on the innovation of their processes through technological development, which are of importance for the region where the analysis was carried out; likewise, the techniques that provide an analysis to detect their needs, centralize efforts and obtain an efficient result must be considered.
Keywords: Carya illinoinensis; optimization; process; production; technological development